Pengaruh Model Pembelajaran Talking Stick terhadap Hasil Belajar Siswa Kelas IV SDN 1 Bendorejo Trenggalek - Rohmatus Syafi'ah; Muttaqin, Mukhammad Zainul; Widiyawati, Amelia Linda (STKIP PGRI Bandar Lampung, 2022)
The results of initial observations, thematic learning in grade IV students of SDN 1 Bendorejo Trenggalek is monotonous and teacher-centered. On average, each sub-theme contains 50% of students who have scores below the KKM. The purpose of this study is to describe the implementation of the talking stick learning model and its effect on student learning outcomes. Methods of data collection using observation and tests. Quantitative research approach with One Group Pretest-Postest Design. The sampling technique used is Nonprobability Sampling with the type of Saturated Sampling, namely all fourth grade students as many as 12 students as respondents. Observations using the learning implementation sheet and hypothesis testing were carried out with the Paired Sample T Test. This is shown from the results of observing the implementation of learning, the percentage of learning implementation is 100%, which means that learning takes place very well and the Paired Sample T Test test obtained a significance value of 0.000 <0.05, which means that there is a difference in the pretest posttest, so there is an effect of the talking stick learning model on the results. student learning.